Impact of Extremely Advanced Maternal Age on Pregnancy Outcomes [35H]. Issue 1 (May 2017) - Hollenbach, Stefanie; Miller, Lauren A.; Olson-Chen, Courtney; Li, Dongmei; Dye, Timothy; Thornburg, Loralei
Abstract : INTRODUCTION: The proportion of women giving birth after the age of 45 has increased significantly over the last several decades for a multitude of reasons. We set out to describe perinatal outcomes for women as pregnancy progresses from advanced (35 or older) to extremely advanced maternal age (45 or older). METHODS: The NYS Perinatal Data System in Upstate New York contains information on 724, 802 pregnancies from 2005-2014. Pregnancy outcomes compared between women less than age 35 and those 35-39, 40-44, 45-49 and 50 and older at delivery. Chi-square testing utilized for categorical variable analysis (significance p-value less than 0.05); odds ratios (OR) calculated for significant comparisons. Significant results were controlled for the use of assistive reproductive technologies (ART) and pre-pregnancy risk factors. RESULTS: A total of 104, 776 women were 35 or older at delivery with 1460 women 45 or older. Compared to women younger than age 35, women 45 or older had increased pre-pregnancy risks including increased pre-gestational diabetes and hypertension (HTN), as well as worse maternal and fetal pregnancy outcomes including preterm birth OR 2.45 (CI 2.15-2.78) and pregnancy-associated HTN OR 1.95 (CI 1.63-2.35). These results were ameliorated but persisted after controlling for multi-fetal gestations, with preterm birth OR 1.65 (CI 1.07-2.55) and pregnancy-associated HTN OR 2.03 (CI 1.25-3.31) remaining more prevalent. CONCLUSION: Maternal and fetal risks increase as maternal age progresses. Increased incidence of multi-fetal gestation contributes to—but does not appear to comprehensively explain—the difference in risk for these women. This has implications for preconception counseling, antepartum care, and delivery planning.